2013
DOI: 10.1111/trf.12125
|View full text |Cite
|
Sign up to set email alerts
|

Babesia microti real‐time polymerase chain reaction testing of Connecticut blood donors: potential implications for screening algorithms

Abstract: We prospectively identified several real-time PCR-positive blood donors, including an IFA-negative real-time PCR-positive donor, in an area highly endemic for B. microti. These results suggest the need to include nucleic acid testing in planned mitigation strategies for B. microti.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…27 Furthermore, exposure to B. microti through tick bites appears to be relatively frequent in endemic regions of the United States as evidenced by seroprevalence rates ranging from 1% to 2.5%. 14,28 This is consistent with our study results that showed that 90% of EIA repeat-reactive donors in endemic areas and 100% in nonendemic areas were PCR and blood smear negative, indicating that the majority of EIA-reactive donors are not likely to be infectious. Such EIA repeat-reactive donors, many of whom have antibodies to B. microti that can be verified by IFA or immunoblot, likely represent individuals with prior, resolved infections and with lingering but waning antibody as demonstrated in other studies.…”
Section: Discussionsupporting
confidence: 90%
“…27 Furthermore, exposure to B. microti through tick bites appears to be relatively frequent in endemic regions of the United States as evidenced by seroprevalence rates ranging from 1% to 2.5%. 14,28 This is consistent with our study results that showed that 90% of EIA repeat-reactive donors in endemic areas and 100% in nonendemic areas were PCR and blood smear negative, indicating that the majority of EIA-reactive donors are not likely to be infectious. Such EIA repeat-reactive donors, many of whom have antibodies to B. microti that can be verified by IFA or immunoblot, likely represent individuals with prior, resolved infections and with lingering but waning antibody as demonstrated in other studies.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies using a short-term in vitro culture as well as immunocompromised mice have shown that, of the four drugs used for treatment of human babesiosis, only atovaquone shows efficacy against the parasite in mouse red blood cells both in vitro and in vivo 11. These results, along with the shortcomings of available diagnostic tools to distinguish between past and active infection to prevent transfusion-transmitted babesiosis, have stimulated efforts to improve therapies and diagnostics111213141516171819.…”
mentioning
confidence: 99%
“…Although the geographic distribution of positive blood donors did not completely overlap with the distribution of the reported clinical cases, a regional screening strategy can be one tool to improve blood safety. Johnson et al [88] identified several NAT-positive, antibody-negative blood donors, which underlines the request for genomic screening systems. Leiby et al [89] reported long-term parasitaemia of T. cruzi in seropositive US blood donors.…”
Section: Discussionmentioning
confidence: 99%